The impact of Work integrated learning on student work-readiness - Smith, C.; Ferns, Sonia; Russell, L. (The Office for Learning and Teaching, 2014)
This project will provide an evidence base for judging the impact of WIL on graduates' readiness to commence work. This will be achieved through: 1. Establishing a conceptualisation of WIL that can be operationalised for measurement and applied equally validly across disciplines and types of WIL; and a conceptualisation of work-readiness that, similarly, is applicable across disciplines. 2. The validation of appropriate measures of these two constructs. 3. Examining the impact of WIL on work-readiness in a wide variety of disciplines and cross a wide range of universities and types of WIL. The knowledge generated about the relationship between WIL and work-readiness will provide a multi-disciplinary evidence base for the impact of WIL on employment-readiness outcomes and guide university leaders in best practice and curricula investment.